Deep Learning Approach to Numeracy Literacy Learning in Elementary Schools - Firdausi, Audi Shafira; Heryani, Rina; Muryanto, Rusdiono (International Conference on Elementary Education, 2025)
Students show that they often cannot apply mathematical knowledge in other fields directly and the teaching and learning activities that occur are dominated by conventional learning, focusing on one-way knowledge transfer from teachers to students, this kind of learning is no longer adequate to meet the demands of the modern era. This article aims to analyze and understand the implementation of numeracy literacy learning at the elementary school level using a deep learning approach to make learning more personal and in-depth. This study uses a qualitative method using data collection techniques with interviews, questionnaires, and literature studies, and data analysis is carried out using analysis techniques according to Miles and Huberman. The data obtained will be subjected to data reduction, data presentation, and drawing conclusions or verification. This study shows that students have an awareness in the use of numbers and symbols, analytical and problem-solving practices, the relevance of learning to everyday life, enjoyable learning experiences, and a positive atmosphere that encourages active involvement.